Effectiveness of School’s Feeding Program in Coping Pupils’ Malnutrition on Their Academic Performance - Bilbar, Armel (IJRDO- Journal of Educational Research, 2020)
This research used the descriptive method to determine the effectiveness of school’s feeding program in coping pupils’ malnutrition on their academic performance in Manduaw Elementary School, Bayawan City Division, Negros Oriental, Philippines. The quantitative data were gathered from the pupils and teachers. Also, the researcher utilized a standardized questionnaire to assess the effectiveness of schools’ feeding program in coping malnutrition on pupils’ academic performance. The statistical tools used in the analysis of the data were percentage, mean, and weighted mean. The study found out that the pupils’ socio-demographic profile have no significant relationship to the academic performance. However, the relationship between the socio-demographic profile of the respondents and the effectiveness school’s feeding program have highly significant relationship on the nutritional status in initial BMI as well as on the nutritional status in Recent BMI. It further concluded that the relationship between school’s feeding program have no significant relationship on the pupils’ academic performance.